Gestión de la cadena de suministro y el desempeño organizacional - Chávez Caiche, Virginia Esmeraldas (2024)
The objective of this thesis is to analyze and improve supply chain management to optimize organizational performance. The research focuses on a company located in Guayaquil, specializing in the distribution of raw materials for the plastics, paper, and chemical industries. The company faces significant issues with the efficiency of raw material deliveries, impacting its competitiveness and customer satisfaction. The proposal includes the implementation of an integrated management system to coordinate all aspects of the production planning process, from sales data collection to production scheduling and inventory management. Additionally, staff training in planning techniques and the use of advanced demand forecasting tools are suggested to anticipate market needs and adjust inventory levels. The adoption of innovative technologies, such as inventory management systems and real-time data analysis, is crucial to improving operational efficiency and decision-making. Implementing lean methodologies and reengineering logistics processes are also recommended to reduce delivery times and enhance customer satisfaction. Finally, evaluating the costbenefit relationship of these improvements will ensure that investments in technology and processes generate tangible value for the organization, strengthening its market position and ensuring long-term competitiveness.